Second-order nonlinear optical properties of X-shaped pyrazine derivatives - Postils, Verònica; Burešová, Zuzana; Casanova, David; Champagne, Benoît; Bureš, Filip; Rodriguez, Vincent; Castet, Frédéric (Royal Society of Chemistry, 2024)
This work reports an investigation of the second-order NLO properties of two isomer series of X-shaped pyrazine derivatives, by means of HRS measurements and DFT calculations. The systems differ in the relative position of the donor and acceptor substituents with respect to the axis formed by the nitrogen atoms of the central pyrazine ring. Although the magnitude of the second harmonic signal is similar, HRS measurements revealed that the anisotropy of the NLO response strongly differs in the two chromophore series, the one of the 2,3-isomers being strikingly dipolar, while the one of the 2,6-isomers is mostly octupolar. The experimental observations are well supported by DFT calculations. In particular, the sum-over-states approach allows us to rationalize the different NLO anisotropies observed in the two isomer series through a detailed analysis of the symmetry of the low-lying excited states. Molecular symmetry controlling NLO-response directionality.
Nelineární optické vlastnosti druhého řádu pyrazinových derivátů struktury písmene X
Keywords: molecular-orbital methods; augmented basis-sets; chromophores; design; hyperpolarizabilities; elements; polarizability; polarization; functionals; performance; chromofory; hyperpolarizabilita; polarizabilita; polarizace; NLO; pyrazin